2018
DOI: 10.1558/japl.35211
|View full text |Cite
|
Sign up to set email alerts
|

Mixed messages in criticisms in Iranian PhD dissertation defenses

Abstract: Taking up the role of examiner in PhD dissertation defense sessions involves dealing with two contradictory desires; namely, effective delivery of criticisms and maintaining a positive interpersonal relationship with the recipients of those criticisms. This study explores the discourse strategies examiners use to express the speech act of criticism in the context of Iranian dissertation defense sessions in English for Academic Purposes. The data come from simplified transcriptions of twelve video-recorded sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…It is worth noting that a number of researchers have realized the influential role genre and institutionalized discourse play in the realization of speech acts. Reference can be made to earlier studies on tutorials (e.g., Hiraga et al, 2003;Hiraga & Turner, 1996) and MA/PhD vivas (e.g., Don & Izadi, 2013;Izadi, 2013Izadi, , 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that a number of researchers have realized the influential role genre and institutionalized discourse play in the realization of speech acts. Reference can be made to earlier studies on tutorials (e.g., Hiraga et al, 2003;Hiraga & Turner, 1996) and MA/PhD vivas (e.g., Don & Izadi, 2013;Izadi, 2013Izadi, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the viva as a context proved useful as "it demonstrates how criticism is accomplished in a speech event in which it is not only a common discourse function but also a sanctionable (if highly constrained) form of behavior" (Don & Izadi, 2013, p. 230). For instance, Don and Izadi (2013) and Izadi (2013Izadi ( , 2014Izadi ( , 2017 revealed that vivas involve a combination of pre-allocated as well as negotiated turns. It was also observed that examiners' criticisms generally start smoothly, but the following criticism responses by MA/PhD candidates, often through defending their theses and clarifying aspects of their work, influence the quality of the subsequent turns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this study, I have chosen two anomalous cases: The first deals with a situation where a supervisor breaches the norms of supervision by aligning with an examiner in attacking the candidate resulting in the co-supervisor's intervention to clash with the supervisor. This interaction has previously been analysed in terms of face (Izadi, 2017a) and has been shown to represent a great deal of relational separation (Arundale, 2010(Arundale, , 2020 between the co-supervisor, the examiner and the supervisor, leading to unconventionally adversarial confrontation. The second represents a case of an examiner arguing with another examiner to defend the candidate, again, an unconventional practice in DDs.…”
Section: Description Of the Datamentioning
confidence: 99%
“…There is a promising line of research on dissertation defences, both universally and in the Iranian culture. Iranian defence sessions have been investigated in terms of a variety of topics, including speech acts (Izadi, 2013a(Izadi, , 2013b(Izadi, , 2018b, and the relational accounts of face and politeness (Don and Izadi, 2011Izadi, , 2013Izadi, 2017aIzadi, , 2017b. Izadi (2018b) observes that talk in dissertation defences in general and criticism-response exchanges in particular feature an equilibrium between the effective delivery of messages (criticisms and disagreeing responses) and maintaining positive interpersonal relationships through paying respect, modulating negative acts, etc.…”
Section: Previous Studies In Dissertation Defencesmentioning
confidence: 99%
See 1 more Smart Citation